Digital corporate communication and crisis life cycles - PANG, A. (Institutional Knowledge at Singapore Management University, 2023)
This chapter argues that digital crisis communication is best studied through the lens of a crisis life cycle. A life cycle provides “an overarching framework” that enables organisations to envision their best options during any stage of the process” (Coombs, 2019, p. 8). While current iterations of life cycles have provided foundational insights, this chapter argues that they may not be sufficient to prepare organisations in the digital age we live in. A Digital Crisis Life Cycle framework - with tactics posited at each phase - is proposed, along with two overarching approaches in corporate communication (i.e. organisational listening and dialogic communication) to help organisations manage the myriad challenges posed by online crises. This framework is applied to a case involving NETS, an electronic payment service provider, to demonstrate how corporations can potentially leverage insights to equip them in digital communication.